Australian wildfire smoke in the stratosphere: the decay phase in 2020/2021 and impact on ozone depletion - Ohneiser, Kevin; Ansmann, Albert; Kaifler, Bernd; Chudnovsky, Alexandra; Barja Gonzalez, Boris; Knopf, Daniel A.; Kaifler, Natalie; Baars, Holger; Seifert, Patric; Villanueva, Diego; Jimenez, Cristofer; Radenz, Martin; et al. (My University, 2022)
Record-breaking wildfires raged in southeastern Australia in late December 2019 and early January 2020. Rather strong pyrocumulonimbus (pyroCb) convection developed over the fire areas and lofted enormous amounts of biomass burning smoke into the tropopause region and caused the strongest wildfire-related stratospheric aerosol perturbation ever observed around the globe. We discuss the geometrical, optical, and microphysical properties of the stratospheric smoke layers and the decay of this major stratospheric perturbation. A multiwavelength polarization Raman lidar at Punta Arenas (53.2 degrees S, 70.9 degrees W), southern Chile, and an elastic backscatter Raman lidar at Rio Grande (53.8 degrees S, 67.7 degrees W) in southern Argentina, were operated to monitor the major record-breaking event until the end of 2021. These lidar measurements can be regarded as representative for mid to high latitudes in the Southern Hemisphere. A unique dynamical feature, an anticyclonic, smoke-filled vortex with 1000 km horizontal width and 5 km vertical extent, which ascended by about 500 m d(-1), was observed over the full last week of January 2020. The key results of the long-term study are as follows. The smoke layers extended, on average, from 9 to 24 km in height. The smoke partly ascended to more than 30 km height as a result of self-lofting processes. Clear signs of a smoke impact on the record-breaking ozone hole over Antarctica in September-November 2020 were found. A slow decay of the stratospheric perturbation detected by means of the 532 nm aerosol optical thickness (AOT) yielded an e-folding decay time of 19-20 months. The maximum smoke AOT was around 1.0 over Punta Arenas in January 2020 and thus 2 to 3 orders of magnitude above the stratospheric aerosol background of 0.005. After 2 months with strongly varying smoke conditions, the 532 nm AOT decreased to 0.03-0.06 from March-December 2020 and to 0.015-0.03 throughout 2021. The particle extinction coefficients at 532 nm were in the range of 10-75 Mm(-1) in January 2020 and, later on, mostly between 1 and 5 Mm(-1). Combined lidar-photometer retrievals revealed typical smoke extinction-to-backscatter ratios of 69 +/- 19 sr (at 355 nm), 91 +/- 17 sr (at 532 nm), and 120 +/- 22 sr (at 1064 nm). An ozone reduction of 20 %-25 % in the 15-22 km height range was observed over Antarctica and New Zealand ozonesonde stations in the smoke-polluted air, with particle surface area concentrations of 1-5 mu m(2) cm(-3).
Keywords: Anticyclone; Tropopause; Ozone Depletion; Middle latitudes